Decision-making governance for purchases of solar photovoltaic systems in Japan. (December 2017) - Tanaka, Kenta; Sekito, Mai; Managi, Shunsuke; Kaneko, Shinji; Rai, Varun
Abstract: In this study, we analyze the factors that affecting purchasing decision time for solar photovoltaic (PV) s in Japan. Based on our survey, consumers spend about 4 months to make purchase decision. Also, our estimation results show that information and knowledge that consumers obtained from the neighborhood and elsewhere make consumers more careful in their decision-making and extend the purchase decision. On the other hand, experts on the advantages and disadvantages of installation shortened the decision time. The situation and environment of each household in terms of income, family size, and the way of purchase of new homes have influenced on the decision to purchase a PV system. In addition, the availability of feed in tariffs was highly correlated with purchasing motivation, but unexpectedly the capital subsidy programs have either little impacts or even delayed impacts on the purchasing timing. Highlights: We analyze the purchasing decision making speed of solar photovoltaic (PV) system. Our results show that decision periods are shortened by feed-in tariffs. Also we find process of behavior to obtain the information affect the decision period.